Investigating the friction, wear and damage behaviour of plain bearing bushes of the variable stator vane system. (January 2022) - Wollmann, T.; Nitschke, S.; Klauke, T.; Behnisch, T.; Ebert, C.; Füßel, R.; Modler, N.; Gude, M.
Abstract: Determining the friction, wear and damage behaviour of aero engine components under realistic operation conditions is important to improve the long-term reliability and efficiency. A special test rig for single plain bearing bushes of the variable stator vane (VSV) system was designed to investigate these components under engine-like conditions. It is found that four main wear and failure phenomena occur during the testing of VSV bushes. These include heavy abrasive wear on the inner contact area, wear on the flange contact area, plastic deformation and material failure as well as heavy wear and debris on the spindle. Results from polyimide-based plain bearing bushes show that the operational torque and wear rate remain almost constant, as long as no failure of the bush occurs. Highlights: Novel test rig for single plain bearing bushes of the variable stator vane system under engine-like conditions. Conditions cover temperature, air pressure and loads for current in-service but also future aero engines. Four main wear and failure phenomena occur during the testing of VSV bushes. Until failure, the operating torque and wear after an initial run-in phase remain almost constant for polyimide-based bushes.